Cyborgization?Emancipation? Cultural Concepts of Technology and Progress in Posthumanist Era - Kopciewicz, Lucyna (INSTED: Interdisciplinary Studies in Education & Society, 2016)
In this paper the author discusses the concept of ?cyborgization? on the level of social prospects, social imagination and educational projects. The ways in which this concept has emerged are discussed and the types of reflection are highlighted which constitute contemporary technological discourses and their impact on society and education. The most important part of the paper focuses on emerging technologies and their educational impact as well as on debates about emancipation of learners.